Śrīharṣa - Jani, A. N.; Sahitya Akademi. (Sahitya Akademi, 1996)
Life and works of Śrīharṣa, 12th cent. poet of India.
Includes bibliographical references (p. [70]-72).
Life and works of Śrīharṣa, 12th cent. poet of India.